Local Wisdom in Stage Houses above the Sea of the Bajo Community, Torosiaje Village Gorontalo Province. - Mohammad Mochsen Sir; Abdul Mannan (Architectural Research Journal, 2023)
Human understanding of nature and forms of human behavior due to its proximity to its ecological elements will foster traditions in human life and produce the local wisdom of the people. Traditional values, attitudes and behavior with an ecological outlook in the local community's way of life become the identity of a community. This local value applies to coastal communities, in fact it is quite effective in managing natural resources and efforts to conserve them. This research is intended to describe life in the values of local wisdom of the Bajo people of Torosiaje Village in Gorontalo. The scope of research includes traditions, behavior and local knowledge of the Bajo community in maintaining ecosystems and utilizing coastal natural resources. Information was obtained through in-depth interviews and focus discussions, in addition to observing community activities and existing coastal ecosystems. Data analysis was carried out in a qualitative descriptive manner. The results showed that the life of the Bajo community in Torosiaje Village was seen in the tradition of going to sea, mamia kadialo, managing settlements, behavior towards catches and community knowledge about marine and coastal natural phenomena.